POTRĄCENIE USTAWOWE W STOSUNKU DO CES JONARIUSZA W ŚWIETLE PRZEPISÓW O PRZELEWIE WIERZYTELNOŚCI - Gutowski, Maciej (Wydział Prawa i Administracji UAM, 2005)
The paper deals with a possibility of a statutory compensation charged upon an assignee of the assigned debt- The aim o f the legal regulation is to establish a certain protection o f the debtor who has no means or power to influence the assignment and who should not bear the risk of transferring the rights without his ¡yiowledge and consent. Further, there is no protection of the certainty of the legal transaction or the assignee's rights who is acting in good faith and takes the position of a creditor, towards whom the debtor does not have any counter, off-balancing receivables. The paper offers a number of possible solution* to compensate the assignment o f receivables in individual phases and evaluates the binding legal regulations regarding that issue.
STATUTORY COMPENSATION CHARGED UPON AN ASSIGNEE IN THE LIGHT OF THE ASSIGNMENT OF DEBT